Affective Behavior in Parent Couples Undergoing Couple Therapy: Contrasting Case Studies - Liekmeier, Esther; Darwiche, Joëlle; Pinna, Lara; Repond, Anne-Sylvie; Antonietti, Jean-Philippe (Frontiers in Psychology, 2021)
Being in a romantic relationship is characterized by a high degree of intimacy and affective involvement. Affective behavior indicates the emotional content in couple interactions and therefore promotes an understanding of the evolution of romantic relationships. When couples are also parents, their affective behavior reflects their romantic and coparental bonds. In this paper, we present an observation of parent couples’ affective behavior during a coparenting conflict discussion task to document whether and how much it improved during couple therapy. Two contrasting cases of affective behavior change are included. Observational coding of affective behavior within pre- and post-intervention coparenting conflict discussion tasks was carried out to compute means and CIs for each partner in both cases. In addition, the partners’ coparental and romantic satisfaction were evaluated through validated self-report questionnaires in pre- and post-intervention assessments; this helped document whether the partners’ coparental and romantic satisfaction were dissimilar between the two cases. Finally, a clinical analysis of both cases was realized with the contribution of the therapists to investigate possible differences within therapy sessions. Statistical analyses revealed negative means of affective behavior for couple A in the pre-intervention assessment and positive means in the post-intervention assessment. Partners from couple B had negative means of affective behavior in the pre- and post-intervention assessments. Results concerning coparental and romantic satisfaction differed: Couple A’s coparental satisfaction slightly increased and the romantic satisfaction somewhat decreased, whereas couple B’s coparental satisfaction remained stable and the romantic satisfaction slightly increased between the pre- and post-intervention assessments. The clinical analysis revealed that the interactional quality of couple A slightly improved within therapy sessions and that both partners succeeded in working together as coparents, notwithstanding their romantic distress. Couple B conveyed coparental distress and exhibited poor interactional quality throughout therapy sessions (e.g., repeated criticism and contempt). This study contributes to enriching the more traditional empirical research methods in the field of couple psychotherapy, as it takes into account microlevel affective changes within parent couples’ interactions in addition to self-reported data. Furthermore, the analysis of therapy sessions supports the importance of working with affective behavior in couple therapy.